2019
DOI: 10.1039/c9nr03952j
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement and anticipation of the Ioffe–Regel crossover in amorphous/nanocrystalline composites

Abstract: Dramatic Ioffe–Regel anticipation for wavepackets propagating in a nanocomposite with strong elastic contrast (right) with respect to amorphous (left).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
47
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(67 citation statements)
references
References 41 publications
(64 reference statements)
7
47
1
Order By: Relevance
“…Recently, we have shown that interfaces affect differently phonons of different wavelengths and frequencies and it is fundamental to look at all phonons relevant for heat transport at a certain temperature, and their perturbed dynamics, for being able to understand thermal conductivity in such nanocomposites [7,29,30]. In that work we could highlight that the rigidity contrast between the two phases is a determinant parameter ruling the strength of the scattering which concerns the phonons with a wavelength comparable with the nanostructuration lengthscale.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have shown that interfaces affect differently phonons of different wavelengths and frequencies and it is fundamental to look at all phonons relevant for heat transport at a certain temperature, and their perturbed dynamics, for being able to understand thermal conductivity in such nanocomposites [7,29,30]. In that work we could highlight that the rigidity contrast between the two phases is a determinant parameter ruling the strength of the scattering which concerns the phonons with a wavelength comparable with the nanostructuration lengthscale.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the most interesting frequency range for the description of thermal transport in amorphous materials is actually the one around and above the Ioffe-Regel limit: when a strong scattering regime arises due to the presence of nanometric elastic heterogeneities, leading to a transition from a ∝ ω 4 to ∝ ω 2 behavior [17,24,27,28,30,38]. Such strong scattering and the resulting diffusive motion of initially plane waves are responsible for the plateau in the glassy thermal conductivity at around 10K, and the peak in the specific heat at the same temperature [14,70,71]. Modeling amorphous materials for thermal applications clearly needs including such frequency dependences, with at least three successive regimes including ∝ ω 2 , ∝ ω 4 and then ∝ ω 2 again at very high frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, they have mostly been investigated by molecular dynamics simulations, allowing the investigation of the competition between the interface effect and the intrinsic acoustic attenuation as due to atomistic mechanisms. Still, the limited sample size in such simulations hinders the reproduction of the real systems and the assumption that what is observed for samples of a few tens of nanometers holds true for larger scales needs to be done [14,[72][73][74]. In a recent work of us, we have taken the opposite approach and we have investigated the acoustic attenuation in nanocomposites through finite-element modeling, which has allowed us to model the real size materials, and study the effect of the interface scattering, highlighting the existence of propagative, diffusive and localized regime, depending on the nanostructuration lengthscale and elastic contrast between the components.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations